Analisa Pemilihan Relai Proteksi Pada Panel Listrik Untuk Studi Kasus Tegangan Menengah 20kV - Intan Nurmalasari; Nur wijayanti; Hin dardi (JURNAL TEKNOLOGI INDUSTRI, 2018)
Relai protection is a component had function in the protection system distribution. As for the relay must be able to work selective, sent to distinguish carefully in overcoming of fault to encourage work of coordination between relai system of protection can work properly.One of the parameter that is the value of setting is as high as protection used for comparison Sepam relay and Micom relay uses ANSI standart 50 / 51 ( Over Current Relay ) and 50N / 51N ( Earth Fault ). Each protection uses two a tripping time curve which is inverse and the definite .From the results of the testing known Micom relay there are failure by 50 % than 10 times testing and in table the results of the time value trip EF 50N known Micom relay there are failure of 30 % than 10 times testing , while there is no invasion of Sepam relay during testing .Of the results of the analysis known recommendations relay match protective meet one of the requirements relay before mounted on the Sepam relay.Keywords: Micom & Sepam Relay Protections, selectivity, OCR & EF.